Resistivity structure of the Link East MT transect in the Southern Curnamona Province. Issue 1 (1st December 2019) - Kay, Ben; Robertson, Kate; Thiel, Stephan; Heinson, Graham
Summary: We present results of 18 magnetotelluric (MT) stations from the Link East transect adjacent to the 03GA-CU1 Curnamona deep crustal seismic reflection line in the southern Curnamona Province, South Australia. The transect was designed to provide resistivity information on the crustal architecture to complement existing datasets and cross the Flinders Conductivity Anomaly (FCA), now known as separate conductors from AusLAMP 3D resistivity models. On the eastern third of the profile, the 10 km site spacing of the profile has allowed us to image two upper crustal conductors (1 Ωm) to the east and west of the Kalkaroo anticline. The eastern conductor (1-4 km depth) is situated in the southern limb of the Mooleulooloo syncline containing Bimba Formation and Strathearn Group sediments, while the western conductor (1-2 km depth) is situated in a small graben comprising Neoproterozoic sediments. On the eastern half, at midcrustal depths ( 15-30 km) a broad conductor (> 20 Ωm) is identified as the southern extension of the Curnamona Conductor with conductive fluid pathways connecting to the upper crustal conductors.